PENGELOLAAN STRES DAN KETERAMPILAN COPING MAHASISWA BARU POLITEKNIK ILMU PELAYARAN MAKASSAR DENGAN MENGGUNAKAN BRIEF COPE: STUDI DESKRIPTIF - Rahmat Permadi; Ince Suryana Arbaina Syafiuddin; Indry Azhary Mangiwa; Cantia Ramdhani (Cahaya Ilmu Bangsa Institute, 2024)
This descriptive study aims to explore stress management and coping skills among first-year students at the Politeknik Ilmu Pelayaran (PIP) Makassar using the Brief COPE instrument. Transitioning from high school to higher education presents significant challenges for new students, particularly in a specialized maritime education environment. This research involved 260 participants, evenly distributed across three majors: Teknika (33.1%), Nautika (33.5%), and Kalk (33.5%). Results reveal that 70.4% of students exhibit moderate coping strategies, while 12.3% fall into the low category, and 17.3% demonstrate high coping abilities. Students in the moderate category show adequate stress management skills, but those in the low category require specific interventions to improve their coping capacity. The findings highlight the significant role of stress and coping mechanisms in supporting students' psychological well-being and academic performance. Consistent with previous research, this study emphasizes the importance of institutional support through problem-based coping training, mentoring programs, and enhanced social support systems. By understanding the unique stress dynamics faced by maritime students, this research contributes to developing targeted interventions to foster a supportive and conducive learning environment.